Death after cure: Mortality among pulmonary tuberculosis survivors in rural Uganda Joseph Baruch Baluku Brenda Namanda Sharon Namiiro Aggrey Byaruhang - Baluku, Joseph Baruch; Namanda, Brenda; Namiiro, Sharon; Rwabwera, Diana Karungi; Mwesigwa, Gloria; Namaara, Catherine; Twinomugisha, Bright; Nyirazihawe, Isabella; Nuwagira, Edwin; Kansiime, Grace; Kizito, Enock; Nabukenya-Mudiope, Mary G; et al. (Elsevier Ltd, 2024)
Objectives: To determine the incidence of mortality and its predictors among pulmonary tuberculosis (PTB) survivors treated at a rural Ugandan tertiary hospital. Methods: We conducted a retrospective chart review of data between 2013 and 2023. We included all people that met the World Health Organisation's definition of tuberculosis cure and traced them or their next of kin to determine vital status (alive/deceased). We estimated the cumulative incidence of mortality per 1000 population, crude all-cause mortality rate per 1000 person-years, and median years of potential life lost for deceased individuals. Using Cox proportional hazard models, we investigated predictors of mortality. Results: Of 334 PTB survivors enrolled, 38 (11.4%) had died. The cumulative incidence of all-cause mortality was 113.7 per 1000 population, and the crude all-cause mortality rate was 28.5 per 1000 person-years. The median years of potential life lost for deceased individuals was 23.8 years (IQR: 9.6-32.8). Hospitalization (adjusted hazard ratio (aHR): 4.3, 95% CI: 1.1-16.6) and unemployment (aHR: 7.04, 95% CI: 1.5-31.6) at TB treatment initiation predicted mortality. Conclusion: PTB survivors experience post high mortality rates after TB cure. Survivors who were hospitalized and unemployed at treatment initiation were more likely to die after cure. Social protection measures and long-term follow-up of previously hospitalized patients could improve the long-term survival of TB survivors.